Meta Analisis Pengaruh Model Pembelajaran Guided Inquiry pada Mata Pelajaran Fisika - Firmansyah Simanjuntak; Sentia Situmorang; Mariati Purnama Simanjuntak (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The purpose of the study was to determine the effect of the guided inquiry learning model in physics learning on learning outcomes, critical thinking skills, process skills, enjoyment/interest, and self-efficacy. The research method used is meta-analysis and literature study, where the population in the study is scientific articles that have been published on guided inquiry learning models in physics subjects. The research sample amounted to 20 articles related to guided inquiry in physics subjects. The data was analyzed by finding the ES. The results showed that student learning outcomes obtained an average of 0.511 in the medium category. The effect on critical thinking skills obtained an average of 1.974 means in the high influence category. The effect on the understanding of physics concepts obtained an average of 4.056, categorized as a high effect. The effect on process skills/investigation obtained an average of 2.3 and is categorized as high. The effect on pleasure/interest in physics obtained an average of 0.748 in the medium category. The effect on self-efficacy obtained 0.188, categorized as less influential. Based on the results of the literature study, it can be concluded that the application of the guided inquiry learning model is an effective and efficient solution because it can improve student learning outcomes if integrated with technology, can improve science literacy, student learning creativity, critical thinking skills, problem solving, psychomotor skills, being active in discussions, and being able to explore in depth the concepts of physics.